Development of Quiz-Based Interactive Learning Videos on the Material of Praiseworthy Morals for Class I of MI Ashabul Kahfi - Firaunal Islam; Fatimah Tuzzahrah; Astuti Kinda; Aisyah Aisyah; Andi Nurindah Sari (Madrasah Al-Wathoniyah : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aimed to develop an interactive quiz-based learning video on the topic of Akhlak Terpuji (commendable morals) for first-grade students at MI Ashabul Kahfi and to describe students' responses to the developed media. This study employed a Research and Development (R&D) approach using the 4D model modified into three stages: define, design, and develop. Data were collected through observation, interviews, and documentation and analyzed using descriptive qualitative techniques. The findings revealed that the learning process in Grade I at MI Ashabul Kahfi was still dominated by the use of whiteboards, indicating the need for more engaging learning media suited to students' characteristics. The learning video was developed using NotebookLM as a tool to generate audio narration, while the learning content and presentation flow were designed by the researcher. The product trial involving 23 students showed positive responses toward the interactive quiz-based learning video. Students became more active, enthusiastic in asking questions, and eager to answer the quizzes embedded in the video. However, several limitations were identified, including insufficient laptop audio volume and the small screen size used during implementation. Overall, the interactive quiz-based learning video can serve as an alternative instructional medium for teaching Akidah Akhlak that is engaging and appropriate for first-grade students.